2011
DOI: 10.1016/j.jmb.2011.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of BamD: An Essential Component of the β-Barrel Assembly Machinery of Gram-Negative Bacteria

Abstract: Folding and insertion of integral β-barrel proteins in the outer membrane is an essential process for Gram-negative bacteria that requires the β-barrel Assembly Machinery (BAM). Efficient OMP folding and insertion appears to require a consensus C-terminal signal in OMPs characterized by terminal F or W residues. The BAM complex is embedded in the outer membrane and, in E. coli, consists of the β-barrel BamA and four lipoproteins BamBCDE. BamA and BamD are broadly distributed across all species of Gram-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
77
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 48 publications
4
77
0
Order By: Relevance
“…However, this conclusion does not imply that each of the >50 different OMPs present in the OM specifically requires BamD for its assembly (39). Other components of the Bam complex also interact with substrates (13,15,(19)(20)(21)(22)38) and may have functions that overlap with that of BamD such that certain OMPs can be assembled in its absence. Rather, we suggest that BamD's essentiality in substrate binding reflects a kinetic effect on In the in vitro experiments, full-length BamA substrates containing mutations in the β-signal sequence were denatured and then diluted into solutions containing 0.5% lauryldimethylamine-N-oxide (LDAO) or BamABCDE proteoliposomes to assess, respectively, the effects of the mutations on the stability of the folded β-barrel and on the folding mechanism carried out by the Bam complex.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…However, this conclusion does not imply that each of the >50 different OMPs present in the OM specifically requires BamD for its assembly (39). Other components of the Bam complex also interact with substrates (13,15,(19)(20)(21)(22)38) and may have functions that overlap with that of BamD such that certain OMPs can be assembled in its absence. Rather, we suggest that BamD's essentiality in substrate binding reflects a kinetic effect on In the in vitro experiments, full-length BamA substrates containing mutations in the β-signal sequence were denatured and then diluted into solutions containing 0.5% lauryldimethylamine-N-oxide (LDAO) or BamABCDE proteoliposomes to assess, respectively, the effects of the mutations on the stability of the folded β-barrel and on the folding mechanism carried out by the Bam complex.…”
Section: Discussionmentioning
confidence: 98%
“…Sam35 and BamD share no obvious sequence homology but perform the same receptor-like function in binding unfolded substrates at the surface of the membrane into which those substrates are inserted (21,30); therefore, the conservation of the β-barrel assembly mechanism extends beyond the steps performed by BamA. Previous reports demonstrating that some mitochondrial β-barrels can be assembled in bacteria and that some bacterial OMPs can be assembled in mitochondria implied that the assembly complexes have similar substrate recognition mechanisms (40)(41)(42)(43), and structural studies (13)(14)(15)(44)(45)(46) suggested that BamD might recognize OMP substrates based on its homology to proteins that bind C-terminal peptides (e.g., a component of the mitochondrial translocase, Tom70; a peroxisomal protein receptor, PEX5; and a factor responsible for organizing Hsp chaperone proteins, Hop). Our results connect these observations and provide the underlying molecular basis for substrate recognition, which explains the reciprocity of β-barrel assembly between mitochondria and bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20) and discrete motifs 21 in the sequences of autotransporters that have been conserved through evolution. One conserved motif referred to as 'the b-motif' 21 , appears to act as targeting sequence recognized by the BAM complex [22][23][24][25][26] . A second conserved 'a-linker motif' was found to be situated within the lumen of several autotransporter barrel domains for which crystal structures are available 21 .…”
mentioning
confidence: 99%